Detection of Li Deposition by Glow Discharge Optical Emission Spectroscopy in Post-Mortem Analysis. (9th July 2015) - Ghanbari, Niloofar; Waldmann, Thomas; Kasper, Michael; Axmann, Peter; Wohlfahrt-Mehrens, Margret
Abstract : Glow discharge optical emission spectroscopy (GD-OES) is employed to detect and quantify Li deposition as a function of depth on graphite electrodes. Commercial cells with graphite anodes were subject to Li plating by being cycled at 5°C. A comparison is made with graphite electrodes with solid electrolyte interphase (SEI) after formation. Depth profiles of O, Li, and C show different surface effects in terms of thickness and Li content, with significantly higher Li concentration in the case of Li deposition.